ANALYZING EFL STUDENTS’ SPEAKING ANXIETY: THE CASE AT ISLAMIC ECONOMY DEPARTMENT OF UIN ALAUDDIN MAKASSAR - Irwanah Jurmasari; Muhammad Azwar Assiddiq; Sri Hariati Mustari (Cakrawala Bahasa, 2021)
This research was conducted to find out the students’ level of anxiety in speaking, the causes of students’ anxiety and the effect of students’ anxiety to speak in speaking class, and the students’ strategies to cope their anxiety in Islamic Economy department of UIN Alauddin Makassar. The results of this research show that the students of Islamic Economy department of UIN Alauddin Makassar were at middle anxious. Moreover, the causes of anxiety for the students with high level anxiety are lack of practice, lack of confidence to speak, unable to speak in front of public, and fear of negative evaluation of peers. Whereas, the students with low level anxiety experience anxiety during speaking class because of competitiveness. The students with high level anxiety have debilitating anxiety with negative effects while the students with low level anxiety have facilitating anxiety. Nevertheless, the students had their own strategies to deal with their anxiety, for example, keeping silent, avoiding eye contact, and smiling or laughing. In addition, the students with low level of anxiety reduce anxiety by practice and preparation. Besides, to reduce anxiety during speaking class, the lecturers gave them motivation to speak English or told the story or jokes.